Longitudinal, strain-specific Staphylococcus aureus introduction and transmission events in households of children with community-associated meticillin-resistant S aureus skin and soft tissue infection: a prospective cohort study. Issue 2 (February 2020) - Mork, Ryan L; Hogan, Patrick G; Muenks, Carol E; Boyle, Mary G; Thompson, Ryley M; Sullivan, Melanie L; Morelli, John J; Seigel, Jennifer; Orscheln, Rachel C; Bubeck Wardenburg, Juliane; Gehlert, Sarah J; Burnham, Carey-Ann D; et al.
Summary: Background: Devising effective, targeted approaches to prevent recurrent meticillin-resistant Staphylococcus aureus (MRSA) skin and soft tissue infection requires an understanding of factors driving MRSA acquisition. We comprehensively defined household longitudinal, strain-level S aureus transmission dynamics in households of children with community-associated MRSA skin and soft tissue infection. Methods: From 2012–15, otherwise healthy paediatric patients with culture-confirmed, community-onset MRSA infections were recruited for the Household Observation of MRSA in the Environment (HOME) prospective cohort study from hospitals and community practices in metropolitan St Louis (MO, USA). Children with health-care-related risk factors were excluded, as determined by evidence of recent hospital admission, an invasive medical device, or residence in a long-term care facility. Household contacts (individuals sleeping in the home ≥four nights per week) and indoor dogs and cats were also enrolled. A baseline visit took place at the index patient's primary home, followed by four quarterly visits over 12 months. At each visit, interviews were done and serial cultures were collected, to detect S aureus from three anatomic sites of household members, two anatomic sites on dogs and cats, and 21 environmental surfaces. Molecular typing was done by repetitive-sequence PCR to define distinct S aureus strains within each household. Longitudinal, multivariable generalised mixed-effects logistic regression models identified factors associated with S aureus acquisition. Findings: Across household members, pets, and environmental surfaces, 1267 strain acquisition events were observed. Acquisitions were driven equally by 510 introductions of novel strains into households and 602 transmissions within households, each associated with distinct factors. Frequent handwashing decreased the likelihood of novel strain introduction into the household (odds ratio [OR] 0·86, credible interval [CrI] 0·74–1·01). Transmission recipients were less likely to own their homes (OR 0·77, CrI 0·63–0·94) and were more likely to share bedrooms with strain-colonised individuals (OR 1·33, CrI 1·12–1·58), live in homes with higher environmental S aureus contamination burden (OR 3·97, CrI 1·96–8·20), and report interval skin and soft tissue infection (OR 1·32, CrI 1·07–1·64). Transmission sources were more likely to share bath towels (OR 1·25, CrI 1·01–1·57). Pets were often transmission recipients, but rarely the sole transmission source. Interpretation: The household environment plays a key role in transmission, a factor associated with skin and soft tissue infection. Future interventions should inclusively target household members and the environment, focusing on straightforward changes in hand hygiene and household sharing behaviours. Funding: National Institutes of Health, Agency for Healthcare Research and Quality, Children's Discovery Institute, Burroughs Wellcome Foundation, Defense Advanced Research Projects Agency.